ЖАҢА ЗАМАН ТАЛАБЫНА САЙ ИММОБИЛИЗДЕНГЕН ПРОБИОТИКАЛЫҚ ПРЕПАРАТТЫ АЛУ (Experimental biology, 2015)
Use of carbonize sorbents (CRS-1) as the carrier of lactobacilli provides address delivery of a probiotic preparation and an attachment to mucous intestines with the subsequent detoxication of a gastroenteric path andnormalization of its microecology.
Keywords: probiotic preparation; microecology